Cross country : a novel - Patterson, James, 1947- (New York : Little, Brown and Co., 2008)
When the home of Alex Cross's oldest friend, Ellie Cox, is turned into the worst murder scene Alex has ever seen, the destruction leads him to believe that he's chasing a horrible new breed of killer.
Keywords: Cross, Alex (Fictitious character) -- Fiction; African American psychologists -- Fiction; Washington (D.C.) -- Fiction; Suspense fiction; Mystery fiction